A New RAM Normalized 1 $f$ -WMS Technique for the Measurement of Gas Parameters in Harsh Environments and a Comparison With ${2f\!/\!1f}$ - Abhishek Upadhyay; Michael Lengden; David Wilson; Gordon Samuel Humphries; Andrew P. Crayford; Daniel G. Pugh; Mark P. Johnson; George Stewart; Walter Johnstone (IEEE Photonics Journal)
A calibration-free first harmonic (1 $f$ ) wavelength modulation spectroscopy (1 $f$ -WMS) technique for gas species parameter measurement is demonstrated. In this technique, the total magnitude of the 1 $f$ -WMS signal is normalized by a component of the 1 $f$ residual amplitude modulation signal. This method preserves the advantages of the traditional $nf\!/\!1f$ -WMS ( $n\geq 2$ ) technique, such as the immunity to the non-absorbing systematic losses and the accurate recovery of gas parameters, without the requirement for non-absorbing regions for normalization at high pressure or high modulation index values (m-values). The proposed technique only requires the 1 $f$ signal, which has the largest magnitude of all the harmonics signals, and, therefore, fundamentally has a higher sensitivity to the $nf\!/\!1f$ technique. Furthermore, since only the 1 $f$ -WMS signal is used, the technique is less complex in terms of signal processing and data acquisition. This paper also shows a comparison of the proposed technique and 2 $f$ /1 $f$ for measuring CO $_2$ in the exhaust of a combuster. The data highlight how nonlinearities in the optical detection system as a function of frequency have a considerable effect on the recovered $2f\!/\!1f$ spectra, causing variation in the recovered gas concentrations. This effect is not seen in the methodology proposed in this paper.